2017
DOI: 10.15761/hec.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Perception of quantity and quality of sleep and their association with health related quality of life and life satisfaction during adolescence

Abstract: Objectives: This study aims to analyse differences between sleep duration and sleep quality and their association with health related quality of life and life satisfaction during adolescence. Methods:The Health Behaviour in School-Aged Children (HBSC) survey is based on a self-completed questionnaire. The participants in the present study were 3631 students (53.1% were girls) in the 8th and 10th grades at school; the mean age was 14.8 years (range 13-18). Results:The present results add to previous ones that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
3
7
0
2
Order By: Relevance
“…Concerning sleep, short sleepers had lower scores of HRQoL compared to healthy sleepers in the present study. This finding is similar to other studies with adolescent samples [ 9 , 23 , 36 ]. Sleep is an important behavior for many body systems, and poor sleep has been associated with impaired emotional regulation and cognitive performance [ 18 ], which can be a pathway that at least partly explains the relationship with HRQoL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Concerning sleep, short sleepers had lower scores of HRQoL compared to healthy sleepers in the present study. This finding is similar to other studies with adolescent samples [ 9 , 23 , 36 ]. Sleep is an important behavior for many body systems, and poor sleep has been associated with impaired emotional regulation and cognitive performance [ 18 ], which can be a pathway that at least partly explains the relationship with HRQoL.…”
Section: Discussionsupporting
confidence: 93%
“…Health-related lifestyle is a determinant of HRQoL [ 5 , 6 ] constituted by many behaviors (e.g., physical activity, screen time, diet, sleep, use of alcohol, tobacco, and other substances) that can positively or negatively affect peoples’ way of life and health [ 7 ], and contribute to the protection or risk for early mortality and chronic diseases [ 8 ]. Adequate sleep has been associated with better HRQoL [ 9 ]. Additionally, recent reviews showed that physical activity [ 6 , 10 , 11 ] and screen time [ 12 ] have been positively and negatively related to HRQoL, respectively, and sports practice has shown to be even better for some of its dimensions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The academic years are a period of vulnerability when considering sleep problems and mental health 1 . Growing evidence suggests poor sleep patterns are related to impaired academic performance 2,3 and lower psychological well-being 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, for sleep, the effects were substantial and involved feeling that one's life is going well, the experience of more positive affect, less negative affect and greater hedonic and emotional wellbeing. More sleep is known to have a positive impact on youth wellbeing and mental health outcomes (Bowers & Moyers, 2017;Chan et al, 2018;Lo et al, 2018;Matos et al, 2017;Yang & Cha, 2018) and is an…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the growing use of ICT is fueling declining levels of wellbeing and mental health (Kleszczewska et al, 2018;Marques et al, 2017;Rees, 2017;Twenge et al, 2018Twenge et al, , 2018; but, others suggest that playing videogames for example, may have positive effects on children's wellbeing (Kovess-Masfety et al, 2016). Physical activity is known to reduce symptoms of mental disorders and improve life satisfaction (Chekroud et al, 2018;Lees & Hopkins, 2013;Schuch et al, 2018;Stanton et al, 2014;Ströhle, 2009); sleep duration is also related to adolescent wellbeing and mental health (Matos et al, 2017;Palmer & Alfano, 2017;Roberts & Duong, 2014;Yang & Cha, 2018). In adults for example, sleep loss has been associated with muted responsiveness to positive events (Sin et al, 2020).…”
Section: Correlates Of Wellbeingmentioning
confidence: 99%